Targeted Delivery of Cytotoxic Drugs: Challenges, Opportunities and New Developments - Cazzamalli, Samuele (Chimia (Aarau), 2017)
Cytotoxic drugs, which are commonly used for the pharmacotherapy of many forms of cancer, often cause substantial toxicity to the patient without being able to induce long-lasting remissions. Ligands specific to accessible tumor-associated targets, capable of selective localization at the neoplastic site, may facilitate the preferential delivery of anti-cancer drugs, boosting activity and helping spare normal organs. In this article, we present a critical analysis of the limitation of conventional anti-cancer drugs and we contrast monoclonal antibodies and small organic ligands, as vehicles for pharmacodelivery applications.